2021
DOI: 10.21037/tlcr-20-727
|View full text |Cite
|
Sign up to set email alerts
|

Can autoantibody tests enhance lung cancer screening?—an evaluation of EarlyCDT®-Lung in context of the German Lung Cancer Screening Intervention Trial (LUSI)

Abstract: Background: Tumor-associated autoantibodies are considered promising markers for early lung cancer detection; so far, however, their capacity to detect cancer has been tested mostly in a clinical context, but not in population screening settings. This study evaluates the early detection accuracy, in terms of sensitivity and specificity, of EarlyCDT ® -Lung-a test panel of seven tumor-associated autoantibodies optimized for lung cancer detection-using blood samples originally collected as part of the German Lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
(48 reference statements)
2
18
0
Order By: Relevance
“…88,89 However, the average age in these studies and pilots was around 65, at which the life-expectancy is 18-22 years. 90 In these studies, self-selection and physician-selection may have aided in reducing the uptake of screening in individuals with low life-expectancies; but within large-scale programs, the uptake of screening in individuals with limited lifeexpectancies may still be considerable. 91 Consequently, discussions are ongoing on how to explicitly incorporate comorbidities and lifeexpectancy in recommendations and shared decision-making for lung cancer screening.…”
Section: Choosing the Risk-thresholdmentioning
confidence: 99%
See 1 more Smart Citation
“…88,89 However, the average age in these studies and pilots was around 65, at which the life-expectancy is 18-22 years. 90 In these studies, self-selection and physician-selection may have aided in reducing the uptake of screening in individuals with low life-expectancies; but within large-scale programs, the uptake of screening in individuals with limited lifeexpectancies may still be considerable. 91 Consequently, discussions are ongoing on how to explicitly incorporate comorbidities and lifeexpectancy in recommendations and shared decision-making for lung cancer screening.…”
Section: Choosing the Risk-thresholdmentioning
confidence: 99%
“…Furthermore, analyses from the German Lung Tumour Screening and Intervention study (LUSI), showed that the EarlyCDT-Lung test had a low sensitivity (13%) for early stage, small tumours as detected by CT screening. 90 In order for biomarkers to be applied in lung cancer screening practice, they need to have improved performance over currently validated risk-prediction models, or provide complementary predictive benefit to these models. Furthermore, they need to provide this information in a cost-effective manner.…”
Section: Potential Applications For Biomarkersmentioning
confidence: 99%
“…In addition to patient factors, the performance of different brands of reagents may also be different. In the Gonzalez Maldonado study, 23 the sensitivity of the EarlyCDT ® ‐Lung‐a test panel of 7‐TAAbs was only 13.0%, and the specificity was 88.9%. In our study, although the sensitivity was higher than theirs, it was still at a low level, indicating that the panel of 7‐TAAbs was not sensitive enough in the diagnosis of early LC.…”
Section: Discussionmentioning
confidence: 96%
“…The EarlyCDT® Lung test has previously been tested in high-risk [20][21][22]. As seen in Table 3, the TAA assay performs best in heavy smokers, patients older than 75 years and late stage disease; sex does not seem to influence outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the EarlyCDT® Lung test was evaluated in the context of the German Lung Cancer Screening Trial (LUSI) [22]. Sensitivity was found to be as low as 13 %.…”
Section: Discussionmentioning
confidence: 99%